2019
DOI: 10.3386/w25907
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Misuse of Income Data and Extreme Poverty in the United States

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…this journal 2012; Bollinger et al forthcoming). Recent work using administrative data has demonstrated that survey data understates the incomes of low-income men and overstates incidence of extreme poverty(Meyer and Mittag 2015;Meyer et al 2018). However, this work tends to confirm the notion that men with a weak attachment to the workforce largely persist on the incomes of other household members.…”
mentioning
confidence: 75%
“…this journal 2012; Bollinger et al forthcoming). Recent work using administrative data has demonstrated that survey data understates the incomes of low-income men and overstates incidence of extreme poverty(Meyer and Mittag 2015;Meyer et al 2018). However, this work tends to confirm the notion that men with a weak attachment to the workforce largely persist on the incomes of other household members.…”
mentioning
confidence: 75%
“…They also adjust for selfemployment, but we have already excluded the lowest-income self-employed people in our figures. These adjustments move many extremely poor people to the deeply poor category, and Meyer et al (2019) find that those moved up by the receipt of inkind benefits appear to be among the most materially deprived Americans.…”
Section: Discussionmentioning
confidence: 96%
“…Some detailed studies on the underreporting of income were carried out in the US. Recent articles by Mittag (2019) and Meyer et al (2019) discuss these adjustments. One method of adjustment for underreporting comes from the Urban Institute's TRIM3 model (Wheaton 2008), which adjusts for the underreporting of some kinds of benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TANF receipt has declined (Danziger 2010;Moffitt 2015;Parolin 2019b), Edin and Shaefer (2015) infer that the 1996 welfare reform contributed to the rise of extreme poverty. In response, a contentious debate has ensued about the levels, trends, and source of deep/extreme poverty (Jencks 2016;Meyer et al 2018;Shaefer and Edin 2018;Winship 2016). For instance, Meyer and colleagues (2018: 1) conclude: "An implication of the low recent level of extreme poverty is that it cannot have risen substantially over time or due to welfare reform.…”
mentioning
confidence: 99%